Development of a cell-based model system for the investigation of ferroptosis - Goebel, Bjarne; Carpanedo, Laura; Reif, Susanne; Göbel, Tamara; Simonyi, Svenja; Schebb, Nils Helge; Steinhilber, Dieter; Häfner, Ann-Kathrin (Frontiers in Cell Death, 2023)
Since 2005, the original three cell death mechanisms apoptosis, autophagy and necrosis are accompanied by several new forms. The most recent member, ferroptosis, was first described in 2012 and is characterized by the accumulation of iron and increased lipid peroxidation. In this study, we present a model system to study ferroptotic states in stably transfected HEK293T cells, using acyl-CoA synthetase long chain family member 4 (ACSL4), a biomarker of ferroptosis, and/or lysophosphatidylcholine acyltransferase 2 (LPCAT2), a transferase responsible for the lipid remodeling process. In addition, we introduced an inducible expression system for 5-lipoxygenase (LO), 15-LO1 and 15-LO2, to trigger enzymatic lipid peroxidation. We characterized the system in terms of ACSL4, LPCAT2 and LO expression both on Western blot level and by laser scanning confocal microscopy as well as the intracellular localization of all enzymes. Furthermore, we verified inducibility and activity of our LOs and, in addition, analyzed non-esterified (free) and total amounts of oxylipins. When cells were incubated with the ferroptosis-inducing agents GPX4 inhibitor RSL3 or GSH reducing erastin, we observed a decrease in cell viability that was strongly enhanced in the presence of ACSL4 and LPCAT2. Interestingly, additional expression of LPCAT2 resulted in altered localization of 15-LO1, which shifted from the cytosol to the nuclear membrane. A similar localization occurred after treatment with RSL3. Therefore, on one hand, we propose that LPCAT2 is an acyltransferase that promotes ferroptotic conditions, and on the other hand, we introduce a new cellbased model system suitable for studying ferroptosis.